Трансценденція та іманенція в політичній теорії й проблема буття людини в політичному світі - Шевчук, Дмитро (Видавництво Львівської політехніки, 2011)
Проаналізовано проблему трансценденції та іманенції в політичній теорії, а також зумовлені цим феномени, а саме політичну теологію та політичне месіанство. Автор звертає увагу на сутність цих феноменів та їх вияви в політичному світі. Крім того, розглянуто вплив політичної теології та політичного месіанства на буття людини в політичному світі, а також визначено способи подолання негативних наслідків такого впливу. In the present article the problem of transcendence and immanence in political theory is analyzed. There are also investigated phenomena of political theology and political messianism that are resulted by transcendence and immanence. The Author pays attention to the essence of these phenomena and to their manifestations in the political world. Moreover, it is examined the influence of political theology and political messianism on the human being in political world, and presented possibilities of overcoming of the negative consequences of such influence.
Transcendence and immanence in political theory and the problem of human’s being in political light
Keywords: трансценденція; іманенція; політична теологія; політичне месіанство; політичний світ; transcendence; immanence; political theology; political messianism; political world